Ethics in archaeobotany: identifying current issues and initiating a declaration of principles - Amaia Arranz-Otaegui; Filipe Costa Vaz; Marian Berihuete-Azorín; Welmoed A. Out; Stéphanie C. Bodin; Naomi F. Miller; Claudia Speciale; João Pedro Tereso; Sabrina Bianco; Maria Rousou; India Ella Dilkes-Hall; Shinya Shoda; et al. (Vegetation History and Archaeobotany, 2026)
This article presents the first systematic assessment of ethical concerns specific to archaeobotanical research, focusing on principles and values. Conducted by an international group of archaeobotanists, the study used an anonymous online survey to document experiences and perceptions within the archaeobotanical community with the aim of raising awareness, identifying prevalent good practices and noting points for improvement. The questionnaire included ten thematic blocks and 63 main questions that covered regulations and guidelines, archaeobotany in excavations, funding, credit and authorship, intellectual property and right to access material, engagement with local communities, research obstacles, misconduct, ecological footprint, and dissemination of research results. We received responses from 114 participants, and the results highlight key challenges, including limited systematic recovery and study of plant remains, scarce funding, unclear decision-making authority, recurrent research misconduct, insufficient benefits for local communities, and low visibility of archaeobotanical research in dissemination and outreach. Building on these findings, we propose a declaration of principles tailored to archaeobotany, outlining the collective commitments of our community. This framework emphasizes safeguarding archaeological plant remains, ethical and rigorous research practices, and equitable participation. By adhering to these principles, archaeobotanists can promote scientific knowledge whilst fostering inclusivity, transparency, and respect for all individuals and communities involved or affected by our research. In this way, the initiative aims to strengthen archaeobotany as a discipline and cultivate a more ethical, inclusive, and collaborative research culture for both current and future generations of archaeobotanists.

Using Bayesian methods to evaluate the diagnostic performance of blood-based diagnostic tests for American cutaneous leishmaniasis and Chagas disease in rural Panamanian dogs in the absence of a gold standard - Kimberly Archbold; Vanessa Pineda; José E. Calzada; Azael Saldaña; Adelys Reina; Alberto Cumbrera; Ayesha Rodríguez; Chystrie Rigg; Caleb Hawkins; Daniel Mendieta; John P. Schmidt; Julie Velásquez Runk; et al. (Veterinary Parasitology, 2026)

Increasing Carbon Availability During Seed Development Could Facilitate Eelgrass Restoration by Bolstering Seed Banks and Increasing Seedling Establishment - A. V. Lowell; A. C. Hall; F. Delany; L. Steele; B. J. Peterson (Estuaries and Coasts, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Metformin reverses oxandrolone-induced anxiety-like behavior and amygdalar neurochemical dysregulation in male rats - Alaa M. Hammad; Sawsan I. Khdair; Ahmad A. Deeb; Yasmeen A. Ibrahim; Taleb M. Hammad; F. Scott Hall (Psychopharmacology, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Relationships Between Soil and Vegetation Properties and Soil Carbon Stocks Differ Between Grasslands with Different Water Table Management - Emma M. N. Polman; Kenneth F. Rijsdijk; Perry Cornelissen; Rutger L. van Hall; Franciska T. de Vries (Ecosystems, 2026)
Water table management such as temporal flooding is an important strategy for influencing vegetation development and creating suitable habitat for wildlife in managed wetland systems. Water table fluctuations can also affect soil carbon and nutrient cycling through changes in abiotic soil properties, plant traits and soil microbial communities, but research on the effect of temporal flooding on these relations is limited. Here we tested the hypothesis that winter inundation leads to a plant community with more fast-growth-related plant traits, a bacterial-dominated soil microbial community, and lower soil organic carbon stocks compared to a year-round dry grassland. We compared soil and vegetation of winter-inundated and non-inundated grassland in a Dutch-managed wetland area. In contrast to our hypothesis, we found that winter inundation results in plant communities with more slow-growth-related traits and microbial communities more dominated by fungi, compared to non-inundated grassland. We found no difference between shallow soil organic carbon stocks, carbon-to-nitrogen ratios or nitrogen-to-phosphorous ratios. Winter inundation did, however, change the relationship between soil and vegetation properties and soil carbon stocks, as well as soil nutrient ratios. While soil carbon stocks in non-inundated grassland were explained by abiotic soil and vegetation properties, soil carbon stocks were only explained by microbial properties in winter-inundated grasslands. These findings show that winter inundation can be used for vegetation and wildlife management with limited effects on soil carbon stocks.

Genetic Diversity and Population Structure in Cities Is Not Consistent Among Cosmopolitan Plant Species - Ava M. Hoffman; Jennifer M. Cocciardi; Prothama Manna; Diego F. Alvarado‐Serrano; Jeannine Cavender‐Bares; Peter M. Groffman; Sharon J. Hall; Sarah E. Hobbie; Susannah B. Lerman; Josep Padullés Cubino; Diane E. Pataki; Tara L. E. Trammell; et al. (Molecular Ecology, 2026)
Urbanisation has led to increasing homogenization of plant communities across cities. However, it is unclear whether these patterns extend to cosmopolitan plant species at the genetic level. We examined genome‐wide genetic patterns in six widespread plant species (three Poaceae and three Asteraceae) across five cities in the USA (Boston, Baltimore, Minneapolis‐St. Paul, Phoenix, and Los Angeles) using reduced‐representation sequencing. We assessed genetic structure, differentiation, and patterns of isolation by distance (IBD) and environment (IBE) to determine if species were genetically homogeneous or differentiated by city, percentage of impervious surface, or both. Most species exhibited limited population structure overall, with Poa annua (annual bluegrass), Taraxacum officinale (dandelion), and Cynodon dactylon (Bermuda grass) showing no significant genetic differentiation among cities, a pattern consistent with high gene flow mediated by human activity. Notable exceptions included city‐level differences in Erigeron canadensis (horseweed) and Lactuca serriola (prickly lettuce), especially in Phoenix. We also observed low genetic diversity in Digitaria sanguinalis (crabgrass) from Phoenix, suggesting recent founder effects or selection via environmental filtering. Erigeron canadensis , the only native species studied, displayed stronger differentiation by city, along with significant isolation by temperature and distance. Among all species, we found no evidence for population structure by impervious surface. Our findings indicate that widespread population genetic structure patterns of cosmopolitan plants are likely to depend more on species attributes (e.g., self‐compatibility) and human‐mediated dispersal than on urbanisation per se.

A history of the collaborative group of the Americas on inherited gastrointestinal cancer (CGA-IGC): 1995–2025 - Beth Dudley; Bruce M. Boman; Marc S. Greenblatt; Steven H. Erdman; Paul E. Wise; Randall E. Brand; Carol A. Burke; Jose G. Guillem; Michael J. Hall; Heather Hampel; Brandie Heald; Matthew F. Kalady; et al. (Familial Cancer, 2026)

Impact of IL-6 and TGF-β1 on equine mesenchymal stromal cell homing gene expression - Jordan L. Parker; Londa J. Berghaus; Julie Gordon; Laura Mathews; Mary Ayobami Akinde; Daniel B. Hall; John F. Peroni (Research in Veterinary Science, 2025)

Population-level phylogenomic analysis yields insights into species cohesion and population substructure of Lobelia section Lobelia (Campanulaceae) - Grant T. Godden; Andrew A. Crowl; Stephen R. Patten; Princess Abu; Svea Hall; Mark O. Johnston; Douglas W. Schemske; T. Wayne Barger; Miguel A. Pérez-Pérez; Christopher R. Herlihy; Lynda F. Delph; Christopher B. Blackwood; et al. (Molecular Phylogenetics and Evolution, 2025)

What’s going on in the livers in my study? Test-item related toxicity or spontaneous finding? - M. Rezaee; P. Hall; S. Rombouts; F. Poosti; L. Ratsamy; J. Ling; R. Fleurance (Journal of Comparative Pathology, 2025)

Beyond Habitat: Memory Versus Environment in Shaping Animal Space Use - Tana L. Verzuh; Kevin L. Monteith; Tayler N. LaSharr; Cody F. Wallace; Rachel A. Smiley; Brittany L. Wagler; Chris Geremia; Katey S. Huggler; Hall Sawyer; Matthew J. Kauffman; Jerod A. Merkle (Ecology Letters, 2025)
For nearly half a century, ecologists have sought to explain animal space use through characteristics of the environment (i.e., habitat). Recent evidence suggests animals also use memory of previous experiences to decide when and where to move. Yet, the relative influence of the two in explaining animal space use has not been resolved. Using six large ungulate species in the Rocky Mountains (USA), we evaluated the performance of a habitat selection model with 16 environmental variables and another with two variables representing previous use (i.e., memory). While memory outperformed the environment for two species and the environment outperformed memory for four species, the influence of memory and the environment was overall comparable. The environment best explained the space use of specialists, while memory best explained species with strong site fidelity. Our work challenges traditional habitat selection theory, showcasing that animals build their spatial preferences through experience just as much as merely responding to their environment.

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Weathering of leaded paint and chromate primer: Transformation of engineered into incidental nanoparticles - Sisara Samaradiwakara; Joel Kroeker; Cynthia Hall; Michael F. Hochella; Michael Schindler (Journal of Hazardous Materials, 2025)

Stabilizing dynamic subsea power cables using Bi-stable nonlinear energy sinks - Anargyros Michaloliakos; Wei-Ying Wong; Ryan Davies; Malakonda Reddy Lekkala; Matthew Hall; Lei Zuo; Alexander F. Vakakis (Ocean Engineering, 2025)

Stoichiometric acclimation of a bacterial parasite to shifts in the diet quality of a single host - Charlotte F. Narr; Scott Binger; Erin Sedlacek; Bianca Anderson; Grace Shoemaker; Adrienne Stanley; Madison Stokoski; Ed K. Hall (Ecology, 2025)
A growing body of literature suggests that the effects of host diet on populations of parasites within a host (i.e., infrapopulations) are dictated by the elemental stoichiometry of the parasite, and new data suggest that the stoichiometric composition of parasites can shift in response to a host's diet. The consequences of this shift in parasite stoichiometry for host–parasite interactions are underexplored. Here, we present evidence that the diet quality of initial “rearing” hosts influences how infrapopulations in subsequent hosts respond to host diet. We reared infrapopulations of the microparasite Pasteuria ramosa in Daphnia magna fed high or low phosphorus (P) diets. Then, because this parasite is transmitted from a spore bank to individual hosts, we pooled spores from hosts within each diet treatment and used them to infect subsequent hosts. We found that P. ramosa had larger spores and achieved higher spore loads when the diet of their new host matched that of their rearing host. We explored the mechanism for this apparent acclimation to host diet by analyzing the stoichiometry of infrapopulations as stoichiometric trait distributions characterized by the mean, functional richness, functional evenness, and functional divergence of spores for each stoichiometric trait carbon (C), nitrogen (N), P, C:N, C:P, and N:P. Both rearing and subsequent host diets altered the stoichiometry of individual spores in subsequent hosts. Furthermore, functional richness in infrapopulation N content explained more variation in the spore load of subsequent hosts (80%) than either of our diet treatments or any other metric of infrapopulation stoichiometry. Our treatments also influenced the parasite's niche. The C:P and N:P trait distributions of infrapopulations consisting of spores exposed to low P diets for two within‐host lifecycles exhibited lower functional evenness and greater functional divergence than those consisting of spores unexposed to low P diets or exposed for one life cycle. Our results demonstrate that parasite rapid acclimation to host diet quality is possible, and quantifying infrapopulation stoichiometry can inform our understanding of host diet effects on host–parasite interactions. Replicating this work across additional host–parasite systems will help resolve the role of such effects in natural systems.

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Rhoifolin as a potential anxiolytic drug for the effects of nicotine withdrawal: beneficial effects on behavior, neuroinflammation, and oxidative stress - Alaa M. Hammad; Suhair Sunoqrot; Thanaa Al-zuhd; Mohammed Waleed; Ali I. M. Ibrahim; F. Scott Hall; Alaa R. Al-Tamimi; Eveen Al-Shalabi (Metabolic Brain Disease, 2025)

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Postglacial Recolonization of the Southern Ocean by Elephant Seals Occurred From Multiple Glacial Refugia - Andrew A. Berg; Megan Askew; Frederik V. Seersholm; Alexander J. F. Verry; A. Rus Hoelzel; Andreanna Welch; Karen Greig; Richard Walter; Michael Knapp; Axel Barlow; Johanna L. A. Paijmans; Jonathan M. Waters; et al. (Global Change Biology, 2025)
The Southern Ocean is warming more rapidly than other parts of our planet. How this region's endemic biodiversity will respond to such changes can be illuminated by studying past events through genetic analyses of time‐series data sets, including historic and fossil remains. Archaeological and subfossil remains show that the southern elephant seal ( Mirounga leonina ) was common along the coasts of Australia and New Zealand in the recent past. This species is now mostly confined to sub‐Antarctic islands and the southern tip of South America. We analyzed ancient seal samples from Australia (Tasmania), New Zealand and the Antarctic mainland to examine how southern elephant seals have responded to a changing climate and anthropogenic pressures during the Holocene. Our analyses show that these seals formed part of a broader Australasian lineage, comprising seals from all sampled locations from the south Pacific sector of the Southern Ocean. Our study demonstrates that southern elephant seal populations have dynamically altered both range and population sizes under climatic and human pressures over surprisingly short evolutionary timeframes for such a large, long‐lived mammal.

Quantifying coral-algal interactions in an acidified ocean: Sargassum spp. exposure mitigates low pH effects on Acropora cervicornis health - Johann D. Lankes; Heather N. Page; Amanda Quasunella; Jaclyn F. Torkelson; Clöe Lemaire; Robert J. Nowicki; Lillia Blasius; Emily R. Hall (Frontiers in Marine Science, 2025)
Increasingly frequent large-scale pelagic Sargassum algae blooms in the Atlantic have become a problem for coastal ecosystems. The mass decay of these blooms reduces water quality for coastal flora and fauna. However, the effects of living Sargassum blooms on seawater quality and consequently coral reef ecosystems that rely on delicately balanced carbonate chemistry are more ambiguous. Future oceans are predicted to be more acidic as additional anthropogenic CO 2 emissions are absorbed, potentially tipping the balance in favor of algal blooms at the cost of coral survival. This study aimed to simulate the indirect interaction between pelagic S argassum spp. and Acropora cervicornis coral fragments from the Florida Reef in current-day and future ocean pH conditions over the course of 70 days in a mesocosm experimental system. Measurements of coral growth and health via buoyant weight and Pulse Amplitude Modulated (PAM) fluorescence measurements reveal an unexpected coral-algal interaction. After 1 month, coral growth was significantly reduced under ocean acidification conditions and exposure to S argassum ; at the same time quantum yield and maximum electron transport rate of photosynthesis were increased relative to control counterparts in ambient and future pH scenarios by up to 14% and 18% respectively. These improvements in photosynthetic efficiency did not translate to significant differences in growth by the final measurement time point. In addition, the presence of Sargassum spp. did not raise seawater pH in the system, raising questions about how it benefited photosynthetic efficiency in exposed corals. Heterotrophy of detrital algal matter is suspected to compensate for impaired photosynthesis of pH stressed corals. Therefore, despite their current negative reputation, Sargassum blooms could provide short term localized benefits to corals in present and future ocean conditions.

Pure CO2 and impure CO2-SO2-NO-O2 reactions with carbon storage site underlying seals: Coaly mudstones and carbonate cemented sandstones - J.K. Pearce; D. Kirste; G.W. Dawson; V. Rudolph; G. Southam; F. Brink; D.J. Paterson; N. Hall; S. Sommacal; S.D. Golding (Science of The Total Environment, 2025)

Development and in-vitro assessment of novel oxygen-releasing feed additives to reduce enteric ruminant methane emissions - Alison Graham; Camilla Thorn; Michael McDonagh; Caroline O'Donnell; Stephen Nolan; Stuart F. Kirwan; Sandra O'Connor; Corine O. Nzeteu; Alejandra C.V. Montoya; Andrew Bartle; Alison Hall; Cathy Abberton; et al. (Science of The Total Environment, 2025)

Comparative receptor modelling for the sources of fine particulate matter (PM2.5) at urban sites in the UK - Deepchandra Srivastava; Supattarachai Saksakulkrai; W. Joe F. Acton; Daniel J. Rooney; James Hall; Siqi Hou; Mark Wolstencroft; Suzanne Bartington; Roy M. Harrison; Zongbo Shi; William J. Bloss (Atmospheric Environment, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Relationships of dog behavior and cattle illness signs to dogs’ ability to distinguish between sick and healthy cattle - Aiden E. Juge; Nathaniel J. Hall; John T. Richeson; Reinaldo F. Cooke; Courtney L. Daigle (Applied Animal Behaviour Science, 2024)

P20-19 Technology-enabled approval acceleration: spotlighting the ICH S1B weight of evidence - F. Hall; A. Bassan; B. Finney (Toxicology Letters, 2024)

P20-10 Embracing regulatory compliance: Genetox meets generation SEND - S. Salazar Arenas; C. Bapat; M. Ellison; M. Wasko; F. Hall (Toxicology Letters, 2024)

Assessing daily patterns in stimulant use during the COVID-19 pandemic in Melbourne, Australia using wastewater analysis - Shuo Chen; Richard Bade; Ben Tscharke; Wayne Hall; Phong Thai; Chang He; Fahad Ahmed; Qiuda Zheng; Phil M. Choi; Jake W. O’Brien; Jochen F. Mueller (Journal of Hazardous Materials, 2024)

Artificial rockpools create habitat refugia on seawalls at high tide - Jessica R. Bone; Alice E. Hall; Rick Stafford; Nazish F. Mir; Jeesa Benny; Roger J.H. Herbert (Ecological Engineering, 2024)

Equipping for risk: Lessons learnt from the UK shale-gas experience on assessing environmental risks for the future geoenergy use of the deep subsurface - P.L. Smedley; G. Allen; B.J. Baptie; A.P. Fraser-Harris; R.S. Ward; R.M. Chambers; S.M.V. Gilfillan; J.A. Hall; A.G. Hughes; D.A.C. Manning; C.I. McDermott; S. Nagheli; et al. (Science of The Total Environment, 2024)

Wastewater-based monitoring of the nitazene analogues: First detection of protonitazene in wastewater - Richard Bade; Dhayaalini Nadarajan; Erin M. Driver; Rolf U. Halden; Cobus Gerber; Alex Krotulski; Wayne Hall; Jochen F. Mueller (Science of The Total Environment, 2024)

Exposure to Sublethal Concentrations of Lead (Pb) Affects Ecologically Relevant Behaviors in House Sparrows (Passer domesticus) - Joseph F. Di Liberto; Simon C. Griffith; Cara J. Hall; Alexandra S. Mendelsohn; John P. Swaddle (Archives of Environmental Contamination and Toxicology, 2024)
Global contamination of environments with lead (Pb) poses threats to many ecosystems and populations. While exposure to Pb is toxic at high concentrations, recent literature has shown that lower concentrations can also cause sublethal, deleterious effects. However, there remains relatively little causal investigation of how exposure to lower concentrations of environmental Pb affects ecologically important behaviors. Behaviors often represent first-line responses of an organism and its internal physiological, molecular, and genetic responses to a changing environment. Hence, better understanding how behaviors are influenced by pollutants such as Pb generates crucial information on how species are coping with the effects of pollution more broadly. To better understand the effects of sublethal Pb on behavior, we chronically exposed adult wild-caught, captive house sparrows ( Passer domesticus ) to Pb-exposed drinking water and quantified a suite of behavioral outcomes: takeoff flight performance, activity in a novel environment, and in-hand struggling and breathing rate while being handled by an experimenter. Compared to controls (un-exposed drinking water), sparrows exposed to environmentally relevant concentrations of Pb exhibited decreases in takeoff flight performance and reduced movements in a novel environment following 9–10 weeks of exposure. We interpret this suite of results to be consistent with Pb influencing fundamental neuro-muscular abilities, making it more difficult for exposed birds to mount faster movements and activities. It is likely that suppression of takeoff flight and reduced movements would increase the predation risk of similar birds in the wild; hence, we also conclude that the effects we observed could influence fitness outcomes for individuals and populations altering ecological interactions within more naturalistic settings.

Radiation cataract in Heterogeneous Stock mice after γ-ray or HZE ion exposure - Norman J. Kleiman; Elijah F. Edmondson; Michael M. Weil; Christina M. Fallgren; Adam King; Catherine Schmidt; Eric J. Hall (Life Sciences in Space Research, 2024)

Global dominance of lianas over trees is driven by forest disturbance, climate and topography - Alain Senghor K. Ngute; David S. Schoeman; Marion Pfeifer; Geertje M. F. van der Heijden; Oliver L. Phillips; Michiel van Breugel; Mason J. Campbell; Chris J. Chandler; Brian J. Enquist; Rachael V. Gallagher; Christoph Gehring; Jefferson S. Hall; et al. (Global Change Biology, 2024)
Growing evidence suggests that liana competition with trees is threatening the global carbon sink by slowing the recovery of forests following disturbance. A recent theory based on local and regional evidence further proposes that the competitive success of lianas over trees is driven by interactions between forest disturbance and climate. We present the first global assessment of liana–tree relative performance in response to forest disturbance and climate drivers. Using an unprecedented dataset, we analysed 651 vegetation samples representing 26,538 lianas and 82,802 trees from 556 unique locations worldwide, derived from 83 publications. Results show that lianas perform better relative to trees (increasing liana‐to‐tree ratio) when forests are disturbed, under warmer temperatures and lower precipitation and towards the tropical lowlands. We also found that lianas can be a critical factor hindering forest recovery in disturbed forests experiencing liana‐favourable climates, as chronosequence data show that high competitive success of lianas over trees can persist for decades following disturbances, especially when the annual mean temperature exceeds 27.8°C, precipitation is less than 1614 mm and climatic water deficit is more than 829 mm. These findings reveal that degraded tropical forests with environmental conditions favouring lianas are disproportionately more vulnerable to liana dominance and thus can potentially stall succession, with important implications for the global carbon sink, and hence should be the highest priority to consider for restoration management.

Standing Litter Modifies Top-Down Effects of Large Herbivores on a Grassland Plant Community - Zhongnan Wang; Zhiwei Zhong; James F. Cahill; Emily M. Holden; Ho Yi Wan; Logan B. Hysen; Ying Gao; Zhaojun Wang; Oyuntsetseg Batlai; J. Hall Cushman; Deli Wang; Xiaofei Li (Ecosystems, 2023)

Phytoremediation as a Tool to Remove Drivers of Antimicrobial Resistance in the Aquatic Environment - Kaniz F. Chowdhury; Rebecca J. Hall; Alan McNally; Laura J. Carter (Reviews of Environmental Contamination and Toxicology, 2023)
Antimicrobials, heavy metals, and biocides are ubiquitous contaminants frequently detected in water bodies across the globe. These chemicals are known as drivers of antimicrobial resistance (AMR), as these chemicals can select for resistance. Tools and processes, are therefore, needed to remove these chemicals from the environment to tackle the environmental component of AMR. Aquatic phytoremediation is a nature-inspired green solution to remove contaminants from the environment. Phytoremediation utilises macrophytes’ ability to sequester and degrade chemical pollutants in aquatic environments. In this review, we define the problem statement by highlighting the presence of AMR drivers in the aquatic environment. We also provide an in-depth review of phytoremediation to tackle chemical pollution by evaluating mechanisms for the removal and degradation of chemicals. This review identifies potential hyper-accumulators and understands how plant species and chemical composition can influence the potential for accumulation. Different pollutants accumulate to different extents in a range of aquatic macrophytes. Therefore, the combined use of floating, submerged and emergent plants would facilitate the optimum removal of AMR drivers considered in this review. A suggested configuration includes Helianthus annus around the edge of a contaminated site, followed by a belt of submerged plants ( Myriophyllum aquaticum ) and a bed of floating plants (e.g., Lemna species) together with the hyperaccumulator, Phragmites australis . Whilst phytoremediation offers a promising option to treat contaminated water, several critical knowledge gaps still exist. The effect of co-exposure to contaminants on the accumulation potential of plants and the fate of antibiotic-resistant genes and bacteria during the phytoremediation process are highlighted in this review. Based on this understanding, targeted areas for future research are proposed.

Monitoring medication and illicit drug consumption in a prison by wastewater-based epidemiology: Impact of COVID-19 restrictions - Zhe Wang; Jochen F. Mueller; Jake W. O'Brien; Jack Thompson; Benjamin J. Tscharke; Rory Verhagen; Qiuda Zheng; Jeremy Prichard; Wayne Hall; Keith Humphreys; Kevin V. Thomas; Phong K. Thai (Water Research, 2023)

P25-13: Polo-like kinase 4 (PLK4) Safety Review – distilling the risks with a rapid augmented intelligence approach - F. Hall; B. Finney (Toxicology Letters, 2023)

Levelling-up rhodolith-bed science to address global-scale conservation challenges - Fernando Tuya; Nadine Schubert; Julio Aguirre; Daniela Basso; Eduardo O. Bastos; Flávio Berchez; Angelo F. Bernardino; Néstor E. Bosch; Heidi L. Burdett; Fernando Espino; Cindy Fernández-Gárcia; Ronaldo B. Francini-Filho; et al. (Science of The Total Environment, 2023)

Impure CO2 storage reactions of sandstone, mudstone and carbonate cemented cores: Experimental CO2 SO2 NOX O2 reaction metal mobilisation and fate - J.K. Pearce; G.W. Dawson; F. Brink; G. Southam; D. Paterson; N. Hall; R. Heath; D. Greer; D. Kirste; S.D. Golding (International Journal of Coal Geology, 2023)

Tracking the southern hemisphere westerlies during and since the last glacial maximum with multiproxy lake records from the Falkland Islands (52 °S) - Meghan Spoth; Brenda Hall; Thomas Lowell; Aaron F. Diefendorf; Megan C. Corcoran; Paul Brickle (Quaternary Science Reviews, 2023)

Gestational organophosphate ester exposure and preschool attention-deficit/hyperactivity disorder in the Norwegian Mother, Father, and Child cohort study - Amber M. Hall; Amanda M. Ramos; Samantha SM. Drover; Giehae Choi; Alexander P. Keil; David B. Richardson; Chantel L. Martin; Andrew F. Olshan; Gro D. Villanger; Ted Reichborn-Kjennerud; Pål Zeiner; Kristin R. Øvergaard; et al. (International Journal of Hygiene and Environmental Health, 2023)

Seismic signature of subduction termination from teleseismic P- and S-wave arrival-time tomography: The case of northern Borneo - S. Pilia; N. Rawlinson; R. Hall; D.G. Cornwell; A. Gilligan; F. Tongkul (Gondwana Research, 2023)

The Birkhead and Murta formations—organic geochemistry and organic petrography of Mesozoic fluvio-lacustrine source rocks in the Eromanga Basin, central Australia - J. Röth; A. Baniasad; F. Froidl; J. Ostlender; C. Boreham; L. Hall; R. Littke (International Journal of Earth Sciences, 2023)
Due to a historic focus on the underlying Cooper Basin and a growing demand for energy in Australia, a reassessment of the Eromanga Basin in central and eastern Australia is necessary, including a more detailed characterization of its Jurassic-Cretaceous petroleum system elements. The Jurassic Birkhead Formation and the Cretaceous Murta Formation are considered the most important source rocks of the Eromanga Basin. To study the petroleum generation potential of these two formations, a set of 55 rock cores from eight petroleum exploration wells was analysed. The sample set was subject to multiple-organic geochemical and petrographical analyses to evaluate organic richness, hydrocarbon potential (Rock–Eval S1 and S2), maceral composition, thermal maturity (e.g. vitrinite reflectance), and saturated and aromatic biomarker composition. The investigated fluvio-lacustrine siltstones and carbonaceous shales exhibit low to excellent total organic carbon (TOC) content, very low sulphur and low inorganic carbon content. Thermal maturity of both formations is at the onset of the oil window (immature to early mature). The Cretaceous Murta Formation shows good hydrocarbon generation potential and, in part, high production indices, while the Jurassic Birkhead Formation generally shows low kerogen to bitumen conversion and a good to very good hydrocarbon generation potential. Dispersed, rather coarse organic matter of terrigenous origin in fine-grained siliciclastic matrix with well-preserved plant remnants including “cutinite flames” is typical. Liptinite (mainly lamalginite) content is generally higher in the Murta Formation (including the occurrence of Botryococcus green algae), while vitrinite is clearly dominant in the Birkhead Formation. The Birkhead solvent extracts exhibit a more heterogeneous distribution of n -alkanes with distinct maxima in the long-chain range, whereas shorter-chain n -alkanes dominate the Murta extracts. Based on their quality and quantity of incorporated organic matter as well as thermal maturity, the petroleum generation potential of the Murta and Birkhead formations is discussed in detail.

Turbulent kinetic energy dissipation rate and associated fluxes in the western tropical Atlantic estimated from ocean glider observations - Peter M. F. Sheehan; Gillian M. Damerell; Philip J. Leadbitter; Karen J. Heywood; Rob A. Hall (Ocean Science, 2023)
Ocean gliders enable us to collect the high-resolution microstructure observations necessary to calculate the dissipation rate of turbulent kinetic energy, ε, on timescales of weeks to months: far longer than is normally possible using traditional ship-based platforms. Slocum gliders have previously been used to this end; here, we report the first detailed estimates of ε calculated using the Batchelor spectrum method on observations collected by a FP07 fast thermistor mounted on a Seaglider. We use these same fast thermistor observations to calculate ε following the Thorpe scale method and find very good agreement between the two methods. The Thorpe scale method yields larger values of ε, but the average difference, which is less than an order of magnitude, is smaller than reported elsewhere. The spatio-temporal distribution of ε is comparable for both methods. Maximum values of ε (10−7 W kg−1) are observed in the surface mixed layer; values of approximately 10−9 W kg−1 are observed between approximately 200 and 500 m depth. These two layers are separated by a 100 m thick layer of low ε (10−10 W kg−1), which is co-located with a high-salinity layer of Subtropical Underwater and a peak in the strength of stratification. We calculate the turbulent heat and salt fluxes associated with the observed turbulence. Between 200 and 500 m, ε induces downward fluxes of both properties that, if typical of the annual average, would have a very small influence on the heat and salt content of the overlying salinity-maximum layer. We compare these turbulent fluxes with two estimates of double-diffusive fluxes that occur in regions susceptible to salt fingers, such as the western tropical Atlantic. We find that the double-diffusive fluxes of both heat and salt are larger than the corresponding turbulent fluxes.

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Methamphetamine-induced lethal toxicity in zebrafish larvae - Yu Chen; Alexander S. Wisner; Isaac T. Schiefer; Frederick E. Williams; F. Scott Hall (Psychopharmacology, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Protective role of lactic acid bacteria and yeasts as dietary carcinogen-binding agents – a review - P. F. Cuevas-González; A. F. González-Córdova; B. Vallejo-Cordoba; J. E. Aguilar-Toalá; F. G. Hall; U. C. Urbizo-Reyes; A. M. Liceaga; A. Hernandez-Mendoza; H. S. García (Critical Reviews in Food Science and Nutrition, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Response to “Connectivity and pore accessibility in models of soil carbon cycling” - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)
Here we respond to Baveye and colleagues' recent critique of our PROMISE model, describing how this new framework significantly advances our understanding of soil spatial heterogeneity and its influence on organic matter transformations.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Response to ‘Stochastic and deterministic interpretation of pool models’ - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

From pools to flow: The PROMISE framework for new insights on soil carbon cycling in a changing world - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2020)
Soils represent the largest terrestrial reservoir of organic carbon, and the balance between soil organic carbon (SOC) formation and loss will drive powerful carbon‐climate feedbacks over the coming century. To date, efforts to predict SOC dynamics have rested on pool‐based models, which assume classes of SOC with internally homogenous physicochemical properties. However, emerging evidence suggests that soil carbon turnover is not dominantly controlled by the chemistry of carbon inputs, but rather by restrictions on microbial access to organic matter in the spatially heterogeneous soil environment. The dynamic processes that control the physicochemical protection of carbon translate poorly to pool‐based SOC models; as a result, we are challenged to mechanistically predict how environmental change will impact movement of carbon between soils and the atmosphere. Here, we propose a novel conceptual framework to explore controls on belowground carbon cycling: P robabilistic R epresentation of O rganic M atter I nteractions within the S oil E nvironment (PROMISE). In contrast to traditional model frameworks, PROMISE does not attempt to define carbon pools united by common thermodynamic or functional attributes. Rather, the PROMISE concept considers how SOC cycling rates are governed by the stochastic processes that influence the proximity between microbial decomposers and organic matter, with emphasis on their physical location in the soil matrix. We illustrate the applications of this framework with a new biogeochemical simulation model that traces the fate of individual carbon atoms as they interact with their environment, undergoing biochemical transformations and moving through the soil pore space. We also discuss how the PROMISE framework reshapes dialogue around issues related to SOC management in a changing world. We intend the PROMISE framework to spur the development of new hypotheses, analytical tools, and model structures across disciplines that will illuminate mechanistic controls on the flow of carbon between plant, soil, and atmospheric pools.

The Vocal Repertoire of the Northern Giant Mouse Lemur (Mirza zaza) in Captivity - Daniel Hending; Melanie Seiler; Kathrin F. Stanger-Hall (International Journal of Primatology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Flight initiation distance changes across landscapes and habitats in a successful urban coloniser - Matthew J. Hall; Alicia L. Burns; John M. Martin; Dieter F. Hochuli (Urban Ecosystems, 2020)

In Silico Prediction and In Vitro Assessment of Multifunctional Properties of Postbiotics Obtained From Two Probiotic Bacteria - J. E. Aguilar-Toalá; F. G. Hall; U. C. Urbizo-Reyes; H. S. Garcia; B. Vallejo-Cordoba; A. F. González-Córdova; A. Hernández-Mendoza; A. M. Liceaga (Probiotics and Antimicrobial Proteins, 2020)

Flood hazard assessment from storm tides, rain and sea level rise for a tidal river estuary - P. M. Orton; F. R. Conticello; F. Cioffi; T. M. Hall; N. Georgas; U. Lall; A. F. Blumberg; K. MacManus (Natural Hazards, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A Growth and Yield Model for Eucalyptus benthamii in the Southeastern United States - Kevin B Hall; Jl Stape; Bronson P Bullock; Doug Frederick; Jeff Wright; Henrique F Scolforo; Rachel Cook (Forest Science, 2019)
In recent Eucalyptus cold-tolerance trials, E. benthamii has shown good growth rates as well as cold tolerance for USDA Plant Hardiness Zones 8 and 9. This study developed growth and yield models for E. benthamii in the southeastern United States. A network of 182 temporary sample plots of E. benthamii ranging in age from 1.5 to 13.3 years was established, and inventory data were collected. Site quality was determined by fitting a polymorphic site index curve, whereas a function for stand basal area based on age, dominant height, and site occupancy was fitted. Stand-level volume and dry-weight biomass prediction equations were fitted as a function of dominant height and basal area. Based on the growth and yield model results, mean annual increments ranged from 26.4 m3 ha–1 year–1 at rotation age 6 years on the best sites to 13.7 m3 ha–1 year–1 at rotation age 10 years on the poorest sites. This is the first published set of management-oriented models for land managers considering planting E. benthamii in the southeastern United States.

Internal waves influence the thermal and nutrient environment on a shallow coral reef - Emma C. Reid; Thomas M. DeCarlo; Anne L. Cohen; George T. F. Wong; Steven J. Lentz; Aryan Safaie; Austin Hall; Kristen A. Davis (Limnology and Oceanography, 2019)
Internal waves can influence water properties in coastal ecosystems through the shoreward transport and mixing of subthermocline water into the nearshore region. In June 2014, a field experiment was conducted at Dongsha Atoll in the northern South China Sea to study the impact of internal waves on a coral reef. Instrumentation included a distributed temperature sensing system, which resolved spatially and temporally continuous temperature measurements over a 4‐km cross‐reef section from the lagoon to 50‐m depth on the fore reef. Our observations show that during summer, internal waves shoaling on the shallow atoll regularly transport cold, nutrient‐rich water shoreward, altering near‐surface water properties on the fore reef. This water is transported shoreward of the reef crest by tides, breaking surface waves and wind‐driven flow, where it significantly alters the water temperature and nutrient concentrations on the reef flat. We find that without internal wave forcing on the fore reef, temperatures on the reef flat could be up to 2.0°C ± 0.2°C warmer. Additionally, we estimate a change in degree heating weeks of 0.7°C‐weeks warmer without internal waves, which significantly increases the probability of a more severe bleaching event occurring at Dongsha Atoll. Furthermore, using nutrient samples collected on the fore reef during the study, we estimated that instantaneous onshore nitrate flux is about four‐fold higher with internal waves than without internal waves. This work highlights the importance of internal waves as a physical mechanism shaping the nearshore environment, and likely supporting resilience of the reef.

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

The relationship between forest cover and diet quality: a case study of rural southern Malawi - C. Hall; J. I. Macdiarmid; R. B. Matthews; P. Smith; S. F. Hubbard; T. P. Dawson (Food Security, 2019)

Restoration Affects Sexual Reproductive Capacity in a Salt Marsh - Scott F. Jones; Erik S. Yando; Camille L. Stagg; Courtney T. Hall; Mark W. Hester (Estuaries and Coasts, 2019)

Comparison of Amsel criteria, Nugent score, culture and two CE-IVD marked quantitative real-time PCRs with microbiota analysis for the diagnosis of bacterial vaginosis - Ellen H. A. van den Munckhof; Rosalie L. van Sitter; Kim E. Boers; Ronald F. Lamont; René te Witt; Saskia le Cessie; Cornelis W. Knetsch; Leen-Jan van Doorn; Wim G. V. Quint; Anco Molijn; Maurine A. Leverstein-van Hall (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Asynchrony in individual and subpopulation fecundity stabilizes reproductive output of an alpine plant population - Ellen Waddle; Lucas R. Piedrahita; Elijah S. Hall; Grace Kendziorski; William F. Morris; Megan L. DeMarche; Daniel F. Doak (Ecology, 2019)
Population‐wide outcomes such as abundance, reproductive output, or mean survival can be stabilized by non‐synchronous variation in the performance of individuals or subpopulations. Such “portfolio effects” have been increasingly documented at the scale of subpopulations and are thought to play an important role in generating stability of population phenomena in the face of environmental variation. However, few studies quantify the strength and origin of portfolio effects at the finer scale of individuals. We used 16 yr of fruit production and climate data for an alpine plant to dissect the scale of portfolio effects in reproduction, as well as the contribution of individual traits including size and flowering time in driving reproductive output. Asynchrony in reproductive success substantially reduces variation in population‐level reproductive output, with approximately one‐fourth of this stabilizing effect arising from individual differences, mostly not those characterized by measured traits, and approximately three‐fourths from asynchrony across subpopulations. These results emphasize the different scales and causes of portfolio effects. The decomposition for portfolio effects we provide can facilitate similar breakdowns of the strength and causes of these effects in other systems.

Emerging threats in addiction: will novel psychoactive substances contribute to exacerbating the ongoing drug overdose epidemic? - F. Scott Hall; Klaus A. Miczek (Psychopharmacology, 2019)

Alcohol and Cocaine Exposure Modulates ABCB1 and ABCG2 Transporters in Male Alcohol-Preferring Rats - Alaa M. Hammad; Fawaz Alasmari; Youssef Sari; F. Scott Hall; Amit K. Tiwari (Molecular Neurobiology, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Soil multifunctionality and drought resistance are determined by plant structural traits in restoring grassland - Ellen L. Fry; Joanna Savage; Amy L. Hall; Simon Oakley; W. J. Pritchard; Nicholas J. Ostle; Richard F. Pywell; James M. Bullock; Richard D. Bardgett (Ecology, 2018)
It is increasingly recognized that belowground responses to vegetation change are closely linked to plant functional traits. However, our understanding is limited concerning the relative importance of different plant traits for soil functions and of the mechanisms by which traits influence soil properties in the real world. Here we test the hypothesis that taller species, or those with complex rooting structures, are associated with high rates of nutrient and carbon (C) cycling in grassland. We further hypothesized that communities dominated by species with deeper roots may be more resilient to drought. These hypotheses were tested in a 3‐yr grassland restoration experiment on degraded ex‐arable land in southern England. We sowed three trait‐based plant functional groups, assembled using database derived values of plant traits, and their combinations into bare soil. This formed a range of plant trait syndromes onto which we superimposed a simulated drought 2 yr after initial establishment. We found strong evidence that community weighted mean ( CWM ) of plant height is negatively associated with soil nitrogen cycling and availability and soil multifunctionality. We propose that this was due to an exploitative resource capture strategy that was inappropriate in shallow chalk soils. Further, complexity of root architecture was positively related to soil multifunctionality throughout the season, with fine fibrous roots being associated with greater rates of nutrient cycling. Drought resistance of soil functions including ecosystem respiration, mineralization, and nitrification were positively related to functional divergence of rooting depth, indicating that, in shallow chalk soils, a range of water capture strategies is necessary to maintain functions. Finally, after 3 yr of the experiment, we did not detect any links between the plant traits and microbial communities, supporting the finding that traits based on plant structure and resource foraging capacity are the main variables driving soil function in the early years of grassland conversion. We suggest that screening recently restored grassland communities for potential soil multifunctionality and drought resilience may be possible based on rooting architecture and plant height. These results indicate that informed assembly of plant communities based on plant traits could aid in the restoration of functioning in degraded soil.

Linear habitats in rural landscapes have complementary roles in bird conservation - Mark Hall; Dale Nimmo; Simon Watson; Andrew F. Bennett (Biodiversity and Conservation, 2018)

Information Seeking and Satisfaction with Information Sources Among Spouses of Men with Newly Diagnosed Local-Stage Prostate Cancer - Aasthaa Bansal; Lisel M. Koepl; Catherine R. Fedorenko; Chunyu Li; Judith Lee Smith; Ingrid J. Hall; David F. Penson; Scott D. Ramsey (Journal of Cancer Education, 2018)

Shelf sea tidal currents and mixing fronts determined from ocean glider observations - Peter M. F. Sheehan; Barbara Berx; Alejandro Gallego; Rob A. Hall; Karen J. Heywood; Sarah L. Hughes; Bastien Y. Queste (Ocean Science, 2018)
Tides and tidal mixing fronts are of fundamental importance to understanding shelf sea dynamics and ecosystems. Ocean gliders enable the observation of fronts and tide-dominated flows at high resolution. We use dive-average currents from a 2-month (12 October–2 December 2013) glider deployment along a zonal hydrographic section in the north-western North Sea to accurately determine M2 and S2 tidal velocities. The results of the glider-based method agree well with tidal velocities measured by current meters and with velocities extracted from the TPXO tide model. The method enhances the utility of gliders as an ocean-observing platform, particularly in regions where tide models are known to be limited. We then use the glider-derived tidal velocities to investigate tidal controls on the location of a front repeatedly observed by the glider. The front moves offshore at a rate of 0.51 km day−1. During the first part of the deployment (from mid-October until mid-November), results of a one-dimensional model suggest that the balance between surface heat fluxes and tidal stirring is the primary control on frontal location: as heat is lost to the atmosphere, full-depth mixing is able to occur in progressively deeper water. In the latter half of the deployment (mid-November to early December), a front controlled solely by heat fluxes and tidal stirring is not predicted to exist, yet a front persists in the observations. We analyse hydrographic observations collected by the glider to attribute the persistence of the front to the boundary between different water masses, in particular to the presence of cold, saline, Atlantic-origin water in the deeper portion of the section. We combine these results to propose that the front is a hybrid front: one controlled in summer by the local balance between heat fluxes and mixing and which in winter exists as the boundary between water masses advected to the north-western North Sea from diverse source regions. The glider observations capture the period when the front makes the transition from its summertime to wintertime state. Fronts in other shelf sea regions with oceanic influence may exhibit similar behaviour, with controlling processes and locations changing over an annual cycle. These results have implications for the thermohaline circulation of shelf seas.

Evaluation of NfsA-like nitroreductases from Neisseria meningitidis and Bartonella henselae for enzyme-prodrug therapy, targeted cellular ablation, and dinitrotoluene bioremediation - Michelle H. Rich; Abigail V. Sharrock; Kelsi R. Hall; David F. Ackerley; Joanna K. MacKichan (Biotechnology Letters, 2018)

Chemical Ecology of Chemosensation in Asteroidea: Insights Towards Management Strategies of Pest Species - Cherie A. Motti; Utpal Bose; Rebecca E. Roberts; Carmel McDougall; Meaghan K. Smith; Michael R. Hall; Scott F. Cummins (Journal of Chemical Ecology, 2018)

Invasion by Rhododendron ponticum depletes the native seed bank with long-term impacts after its removal - Janet E. Maclean; Ruth J. Mitchell; David F. R. P. Burslem; David Genney; Jeanette Hall; Robin J. Pakeman (Biological Invasions, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

Discovery of new orbiviruses and totivirus from Anopheles mosquitoes in Eastern Australia - Agathe M. G. Colmant; Kayvan Etebari; Cameron E. Webb; Scott A. Ritchie; Cassie C. Jansen; Andrew F. van den Hurk; Helle Bielefeldt-Ohmann; Jody Hobson-Peters; Sassan Asgari; Roy A. Hall (Archives of Virology, 2017)

Antifungal genes expressed in transgenic pea (Pisum sativum L.) do not affect root colonization of arbuscular mycorrhizae fungi - Jagroop Gill Kahlon; Hans-Jörg Jacobsen; James F. Cahill; Linda M. Hall (Mycorrhiza, 2017)

Providing Health Information to Latino Farmworkers: The Case of the Affordable Care Act - Thomas A. Arcury; Anna Jensen; Mackenzie Mann; Joanne C. Sandberg; Melinda F. Wiggins; Jennifer W. Talton; Mark A. Hall; Sara A. Quandt (Journal of Agromedicine, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Odorant receptors and antennal lobe morphology offer a new approach to understanding olfaction in the Asian longhorned beetle - Robert F. Mitchell; Loyal P. Hall; Peter F. Reagel; Duane D. McKenna; Thomas C. Baker; John G. Hildebrand (Journal of Comparative Physiology A, 2017)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Causes of WRF surface energy fluxes biases in a stratocumulus region - A. Jousse; A. Hall; F. Sun; J. Teixeira (Climate Dynamics, 2016)

Forest restoration following surface mining disturbance: challenges and solutions - S. Ellen Macdonald; Simon M. Landhäusser; Jeff Skousen; Jennifer Franklin; Jan Frouz; Sarah Hall; Douglass F. Jacobs; Sylvie Quideau (New Forests, 2015)

Sex differences in the effects of adolescent social deprivation on alcohol consumption in μ-opioid receptor knockout mice - Yuki Moriya; Yoshiyuki Kasahara; F. Scott Hall; Yasufumi Sakakibara; George R. Uhl; Hiroaki Tomita; Ichiro Sora (Psychopharmacology, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Developmental alterations in anxiety and cognitive behavior in serotonin transporter mutant mice - Yasufumi Sakakibara; Yoshiyuki Kasahara; F. Scott Hall; Klaus-Peter Lesch; Dennis L. Murphy; George R. Uhl; Ichiro Sora (Psychopharmacology, 2014)

Environmental Factors Affecting Germination and Seedling Survival of Carolina Willow (Salix Caroliniana) - Luz M. Castro-Morales; Pedro F. Quintana-Ascencio; John E. Fauth; Kimberli J. Ponzio; Dianne L. Hall (Wetlands, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Statistical analysis of winter ozone events - Marc L. Mansfield; Courtney F. Hall (Air Quality, Atmosphere & Health, 2013)

Increased competition does not lead to increased phylogenetic overdispersion in a native grassland - Jonathan A. Bennett; Eric G. Lamb; Jocelyn C. Hall; Warren M. Cardinal‐McTeague; James F. Cahill (Ecology Letters, 2013)
That competition is stronger among closely related species and leads to phylogenetic overdispersion is a common assumption in community ecology. However, tests of this assumption are rare and field‐based experiments lacking. We tested the relationship between competition, the degree of relatedness, and overdispersion among plants experimentally and using a field survey in a native grassland. Relatedness did not affect competition, nor was competition associated with phylogenetic overdispersion. Further, there was only weak evidence for increased overdispersion at spatial scales where plants are likely to compete. These results challenge traditional theory, but are consistent with recent theories regarding the mechanisms of plant competition and its potential effect on phylogenetic structure. We suggest that specific conditions related to the form of competition and trait conservatism must be met for competition to cause phylogenetic overdispersion. Consequently, overdispersion as a result of competition is likely to be rare in natural communities.

An evaluation of the serotonin system and perseverative, compulsive, stereotypical, and hyperactive behaviors in dopamine transporter (DAT) knockout mice - Meredith A. Fox; Micaella G. Panessiti; F. Scott Hall; George R. Uhl; Dennis L. Murphy (Psychopharmacology, 2013)

Impaired cliff avoidance reaction in dopamine transporter knockout mice - Motoyasu Yamashita; Yasufumi Sakakibara; F. Scott Hall; Yohtaro Numachi; Sumiko Yoshida; Hideaki Kobayashi; Osamu Uchiumi; George R. Uhl; Yoshiyuki Kasahara; Ichiro Sora (Psychopharmacology, 2013)

The trouble with deficits - Elizabeth F. Hall; Todd Sanders (Climatic Change, 2013)

Spatial variation of phytoplankton assemblages and biomass in the New Zealand sector of the Southern Ocean during the late austral summer 2008 - F. Hoe Chang; Michael J. M. Williams; Jill N. Schwarz; Julie A. Hall; Elizabeth W. Maas; Rob Stewart (Polar Biology, 2013)

Small-business demise and recovery after Katrina: rate of survival and demise - Holly L. Schrank; Maria I. Marshall; Adrienne Hall-Phillips; Renee F. Wiatt; Nicole E. Jones (Natural Hazards, 2013)

Erratum to: Simulating cold season snowpack: Impacts of snow albedo and multi-layer snow physics - D. Waliser; J. Kim; Y. Xue; Y. Chao; A. Eldering; R. Fovell; A. Hall; Q. Li; K. N. Liou; J. McWilliams; S. Kapnick; R. Vasic; et al. (Climatic Change, 2013)

Sharing Heterogeneous Data: The National Database for Autism Research - Dan Hall; Michael F. Huerta; Matthew J. McAuliffe; Gregory K. Farber (Neuroinformatics, 2012)

Pleistocene biogeochemical record in the south‐west Pacific Ocean (images site MD97‐2114, Chatham Rise) - M. Cobianchi; V. Luciani; C. Lupi; N. Mancin; F. Lirer; N. Pelosi; I. Trattenero; M. Bordiga; I. R. Hall; M. Sprovieri (Journal of Quaternary Science, 2012)
Through a multidisciplinary approach based on novel micropaleontological and geochemical analyses, the main paleoceanographic and paleoclimate changes that have influenced the surface‐ and deep‐water circulation in the SW Pacific Ocean (Chatham Rise, eastern New Zealand) during the last million years are reconstructed. This region represents a key area for investigating the climate evolution during the Pleistocene because here the largely wind‐driven Antarctic Circumpolar Current interacts with the west Pacific Ocean circulation via the Deep Western Boundary Current, the major source of deep water for the whole Pacific Ocean. To understand coupling or decoupling events between sea surface and bottom waters, a continuous marine sedimentary succession since 1.1 Ma, recovered by the IMAGES (International Marine Past Global Change Study) cruise in the SW Pacific Ocean (Core MD97‐2114), has been investigated based on calcareous planktonic and benthic microfossil content and C and O isotope record performed on planktonic and benthic foraminiferal tests. Results show the occurrence of long‐ and short‐term patterns of climate and ocean circulation in the last million years as the result of the interplay of ice‐sheet dynamics, surface tropical versus polar water inflow, and trophic status of the surface water. Copyright © 2012 John Wiley & Sons, Ltd.

Angiotensin converting enzyme 2 abrogates bleomycin-induced lung injury - G. J. Rey-Parra; A. Vadivel; L. Coltan; A. Hall; F. Eaton; M. Schuster; H. Loibner; J. M. Penninger; Z. Kassiri; G. Y. Oudit; B. Thébaud (Journal of Molecular Medicine, 2012)

Effects of neurotensin gene knockout in mice on the behavioral effects of cocaine - F. Scott Hall; Marjorie Centeno; Maria T. G. Perona; Jordan Adair; Paul R. Dobner; George R. Uhl (Psychopharmacology, 2012)

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

Simulating cold season snowpack: Impacts of snow albedo and multi-layer snow physics - D. Waliser; J. Kim; Y. Xue; Y. Chao; A. Eldering; R. Fovell; A. Hall; Q. Li; K. N. Liou; J. McWilliams; S. Kapnick; R. Vasic; et al. (Climatic Change, 2011)

Characterisation of the Poly-(Vinylpyrrolidone)-Poly-(Vinylacetate-Co-Crotonic Acid) (PVP:PVAc-CA) Interpolymer Complex Matrix Microparticles Encapsulating a Bifidobacterium lactis Bb12 Probiotic Strain - C. I. Mamvura; F. S. Moolman; L. Kalombo; A. N. Hall; M. S. Thantsha (Probiotics and Antimicrobial Proteins, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Paleoredox status and thermal alteration of the lower Cambrian (Series 2) Emu Bay Shale Lagerstätte, South Australia - D. M. McKirdy; P. A. Hall; C. Nedin; G. P. Halverson†; B. H. Michaelsen; J. B. Jago; J. G. Gehling; R. J. F. Jenkins (Australian Journal of Earth Sciences, 2011)

Modeling the Effect of Midrotation Fertilization on Specific Gravity of Loblolly Pine ( Pinus taeda L.) - Finto Antony; Laurence R. Schimleck; Daniel B. Hall; Alexander Clark; Richard F. Daniels (Forest Science, 2011)
Ring specific gravity, earlywood and latewood specific gravity, and percent latewood were measured on cores collected at breast height from a thinned and fertilized midrotation loblolly pine (Pinus taeda L.) plantation in the lower Coastal Plain of North Carolina. The study was laid out in a randomized complete block design receiving four levels of nitrogen (N) fertilizer in 1984: 000 (control), 112, 224, and 336 kg/ha plus 28 kg/ha of phosphorus with each treatment. A consistent pattern of response was observed in latewood specific gravity (LWSG) after the application of different levels of fertilizer and used as a variable for modeling. The LWSG profiles of unfertilized trees followed a nonlinear relation with ring number from pith. A three-parameter asymptotic function was used to explain the LWSG profile of unfertilized trees with ring number as a covariate. Application of N reduced LWSG and was modeled using a two-parameter response function with year since fertilization as a covariate and separate parameter estimates for each fertilization level. On the basis of the model, the magnitude of maximum cumulative response was −0.025, −0.049, and −0.074 attained at 3.7, 1.9, and 0.8 years after fertilization for the 112, 224, and 336 kg/ha treatments, respectively.

Linking Microbial and Ecosystem Ecology Using Ecological Stoichiometry: A Synthesis of Conceptual and Empirical Approaches - E. K. Hall; F. Maixner; O. Franklin; H. Daims; A. Richter; T. Battin (Ecosystems, 2011)

Evidence of susceptibility to morbillivirus infection in cetaceans from the United States - T. K. Rowles; L. S. Schwacke; R. S. Wells; J. T. Saliki; L. Hansen; A. Hohn; F. Townsend; R. A. Sayre; A. J. Hall (Marine Mammal Science, 2011)
Cetacean morbilliviruses (CeMV) are viruses that can cause mass mortalities among various odontocete species. In this study levels of “herd” immunity in cetaceans from the U.S. coast are described from the distribution and prevalence of antibodies against morbilliviruses. Neutralizing antibody titers against dolphin morbillivirus (DMV), porpoise morbillivirus (PMV), phocine distemper (PDV), and canine distemper viruses (CDV) were measured. Positive samples had higher titers against the CeMV than against the other morbilliviruses tested, indicating that although PDV or CDV can be used to investigate exposure their use may result in a higher false negative rate. The results suggest that morbillivirus did not persist in coastal populations of bottlenose dolphins ( Tursiops truncatus ) after the major outbreaks that occurred in the 1980s and 1990s. Bottlenose dolphins from Beaufort, North Carolina; St. Joseph Bay, Florida; and Cape May, New Jersey had anti‐DMV seroprevalences ranging from between 15% and 33% but those from Charleston, South Carolina and Sarasota Bay, Florida, sampled in recent years were largely negative. These latter groups are therefore now vulnerable to infection and could experience high mortality if exposed to CeMV. Sero‐surveys of this kind are therefore vital for assessing the risk of new and recurring viral outbreaks in coastal cetaceans.

Effects of ocean acidification on invertebrate settlement at volcanic CO2 vents - M. Cigliano; M. C. Gambi; R. Rodolfo-Metalpa; F. P. Patti; J. M. Hall-Spencer (Marine Biology, 2010)

Invasion and production of New Zealand mud snails in the Colorado River, Glen Canyon - Wyatt F. Cross; Emma J. Rosi-Marshall; Kathrine E. Behn; Theodore A. Kennedy; Robert O. Hall; A. Elizabeth Fuller; Colden V. Baxter (Biological Invasions, 2010)

Idealized tracer transport models with time-varying transport: applications to ocean boundary currents - F. Terenzi; Timothy M. Hall (Environmental Fluid Mechanics, 2010)

A multidisciplinary study of archaeological grape seeds - Enrico Cappellini; M. Thomas P. Gilbert; Filippo Geuna; Girolamo Fiorentino; Allan Hall; Jane Thomas-Oates; Peter D. Ashton; David A. Ashford; Paul Arthur; Paula F. Campos; Johan Kool; Eske Willerslev; et al. (The Science of Nature, 2010)

Competitive PCR reveals the complexity of postcopulatory sexual selection in Teleogryllus commodus - MATTHEW D. HALL; LUC F. BUSSIÈRE; MARCO DEMONT; PAUL I. WARD; ROBERT C. BROOKS (Molecular Ecology, 2010)

Reactivation of BK polyomavirus in patients with multiple sclerosis receiving natalizumab therapy - Roisin M Lonergan; Michael J Carr; Cillian F De Gascun; Lisa F Costelloe; Allison Waters; Suzie Coughlan; Marguerite Duggan; Katie Doyle; Sinead Jordan; Michael W Hutchinson; William W Hall; Niall J Tubridy (Journal of NeuroVirology, 2009)

Estimating habitat selection when GPS fix success is less than 100% - Ryan M. Nielson; Bryan F. J. Manly; Lyman L. McDonald; Hall Sawyer; Trent L. McDonald (Ecology, 2009)
Inferences about habitat selection by animals derived from sequences of relocations obtained with global positioning system (GPS) collars can be influenced by GPS fix success. Environmental factors such as dense canopy cover or rugged terrain can reduce GPS fix success, making subsequent modeling problematic if fix success depends on the selected habitat. Ignoring failed fix attempts may affect estimates of model coefficients and lead to incorrect conclusions about habitat selection. Here, we present a habitat selection model that accounts for missing locations due to habitat‐induced data losses, called a resource selection function (RSF) for GPS fix success. The model's formulation is similar to adjusting estimates of probability of occupancy when detection is less than 100% in patch occupancy sampling. We demonstrate use of the model with GPS data collected from an adult female mule deer ( Odocoileus hemionus ) and discuss how to analyze data from multiple animals. In the simulations presented, our habitat selection model was generally unbiased for GPS data sets missing up to 50% of the locations.

Sigma1 receptor antagonists determine the behavioral pattern of the methamphetamine-induced stereotypy in mice - J. Kitanaka; N. Kitanaka; T. Tatsuta; F. S. Hall; G. R. Uhl; K. Tanaka; N. Nishiyama; Y. Morita; M. Takemura (Psychopharmacology, 2009)

Small-Molecule Mediated Neuroprotection in an In Situ Model of Tauopathy - Nicolette S. Honson; Jordan R. Jensen; Aida Abraha; Garth F. Hall; Jeff Kuret (Neurotoxicity Research, 2009)

Minimum Flows and Levels Method of the St. Johns River Water Management District, Florida, USA - Clifford P. Neubauer; Greeneville B. Hall; Edgar F. Lowe; C. Price Robison; Richard B. Hupalo; Lawrence W. Keenan (Environmental Management, 2008)

Neuroimaging of mirtazapine enantiomers in humans - Donald F. Smith; Søren B. Hansen; Steen Jakobsen; Dirk Bender; Hélène Audrain; Mahmoud Ashkanian; Bo S. Stork; Luciano Minuzzi; Håkan Hall; Raben Rosenberg (Psychopharmacology, 2008)

Drag-reducing polysaccharides from marine microalgae: species productivity and drag reduction effectiveness - K. Gasljevic; K. Hall; D. Chapman; E. F. Matthys (Journal of Applied Phycology, 2008)

Improved topographic correction of forest image data using a 3‐D canopy reflectance model in multiple forward mode - S. A. Soenen; D. R. Peddle; C. A. Coburn; R. J. Hall; F. G. Hall (International Journal of Remote Sensing, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Methamphetamine-induced locomotor activity and sensitization in dopamine transporter and vesicular monoamine transporter 2 double mutant mice - Setsu Fukushima; Haowei Shen; Harumi Hata; Arihisa Ohara; Kayo Ohmi; Kazutaka Ikeda; Yohtaro Numachi; Hideaki Kobayashi; F. Scott Hall; George R. Uhl; Ichiro Sora (Psychopharmacology, 2007)

Focusing of phytodetritus deposition beneath a deep‐ocean front, Chatham Rise, New Zealand - Scott D. Nodder; Gerard C. A. Duineveld; Conrad A. Pilditch; Philip J. Sutton; P. Keith Probert; Marc S. S. Lavaleye; Rob Witbaard; F. Hoe Chang; Julie A. Hall; Ken M. Richardson (Limnology and Oceanography, 2007)
In October 2001, we observed a deep‐ocean phytodetritus deposition event on Chatham Rise beneath the Subtropical Front (STF). The origin of this phytodetritus was probably an extensive phytoplankton bloom that occurred in the STF in the preceding weeks. We assessed the spatial distribution of the deposition event using video images from benthic lander and epibenthic trawl deployments and sediment pigment analyses at six sites on a north—south transect across Chatham Rise. High surficial sediment chlorophyll a concentrations were restricted spatially to the southern flank of Chatham Rise (350–1,200‐m depth) with the highest values centered at ~750‐m water depth (750 S). This southern 750 S site was also the only site where macroscopic phytodetritus was observed, coincident with elevated benthic biomass and sediment community respiration rates. At 750 S, phytodetritus resuspension was observed on video and corroborated by current meter, sediment trap, and optical backscatter measurements, suggesting a threshold erosion current speed for phytodetritus of ~10 cm s −1 , equivalent to a shear velocity of 0.5 cm s −1 and similar to other deep‐ocean studies elsewhere. The restriction of macroscopic phytodetritus deposition to 750 S was related to a zone of current convergence within the STF and lower near‐bed current speeds observed across ~1‐day that promoted deposition. Observations of high benthic biomass and respiration on the southern flank of Chatham Rise suggest that this focusing process is important in fueling the energy demands of benthic communities, in association with the general west‐east advection of organic matter within the STF itself. Such physical focusing of labile organic matter deposition may be an important process in other highly productive frontal systems.

Invasion in a heterogeneous world: resistance, coexistence or hostile takeover? - Brett A. Melbourne; Howard V. Cornell; Kendi F. Davies; Christopher J. Dugaw; Sarah Elmendorf; Amy L. Freestone; Richard J Hall; Susan Harrison; Alan Hastings; Matt Holland; Marcel Holyoak; John Lambrinos; et al. (Ecology Letters, 2007)
We review and synthesize recent developments in the study of the invasion of communities in heterogeneous environments, considering both the invasibility of the community and impacts to the community. We consider both empirical and theoretical studies. For each of three major kinds of environmental heterogeneity (temporal, spatial and invader‐driven), we find evidence that heterogeneity is critical to the invasibility of the community, the rate of spread, and the impacts on the community following invasion. We propose an environmental heterogeneity hypothesis of invasions, whereby heterogeneity both increases invasion success and reduces the impact to native species in the community, because it promotes invasion and coexistence mechanisms that are not possible in homogeneous environments. This hypothesis could help to explain recent findings that diversity is often increased as a result of biological invasions. It could also explain the scale dependence of the diversity–invasibility relationship. Despite the undoubted importance of heterogeneity to the invasion of communities, it has been studied remarkably little and new research is needed that simultaneously considers invasion, environmental heterogeneity and community characteristics. As a young field, there is an unrivalled opportunity for theoreticians and experimenters to work together to build a tractable theory informed by data.

Risk factors for incident Alzheimer's disease in African Americans and Yoruba - A. Ogunniyi; K. S. Hall; O. Gureje; O. Baiyewu; S. Gao; F. W. Unverzagt; V. Smith-Gamble; R. E. Evans; J. Dickens; B. S. Musick; H. C. Hendrie (Metabolic Brain Disease, 2006)

Genetic variation at the growth hormone (GH1) and growth hormone receptor (GHR) loci as a risk factor for hypertension and stroke - Martin Horan; Vicky Newsway; Yasmin; Mark D. Lewis; Tammy E. Easter; D. Aled Rees; Arti Mahto; David S. Millar; Annie M. Procter; Maurice F. Scanlon; Ian B. Wilkinson; Ian P. Hall; et al. (Human Genetics, 2006)

Lake Sediment Core Records of Sulphur Accumulation and Sulphur Isotopic Composition in Central Ontario, Canada Lakes - M. Catherine Eimers; Andrew M. Paterson; Peter J. Dillon; Sherry L. Schiff; Brian F. Cumming; Roland I. Hall (Journal of Paleolimnology, 2006)

Avoiding Dangerous Anthropogenic Interference with the Climate System - Klaus Keller; Matt Hall; Seung-Rae Kim; David F. Bradford; M. Oppenheimer (Climatic Change, 2005)

Potential Beneficial Metabolic Interactions Between Tamoxifen and Isoflavones via Cytochrome P450-mediated Pathways in Female Rat Liver Microsomes - Jun Chen; Steven C. Halls; Joshua F. Alfaro; Zhaohui Zhou; Ming Hu (Pharmaceutical Research, 2004)

Sugarbeet Yield Monitoring for Site-Specific Farming Part II–Field Testing - T. L. Hall; L. F. Backer; V. L. Hofman; L. J. Smith (Precision Agriculture, 2003)

Armenian Y chromosome haplotypes reveal strong regional structure within a single ethno-national group - Michael E. Weale; Levon Yepiskoposyan; Rolf F. Jager; Nelli Hovhannisyan; Armine Khudoyan; Oliver Burbage-Hall; Neil Bradman; Mark G. Thomas (Human Genetics, 2001)

Female Sex Pheromone of Brinjal Fruit and Shoot Borer, Leucinodes orbonalis Blend Optimization - A. Cork; S. N. Alam; A. Das; C. S. Das; G. C. Ghosh; D. I. Farman; D. R. Hall; N. R. Maslen; K. Vedham; S. J. Phythian; F. M. A. Rouf; K. Srinivasan (Journal of Chemical Ecology, 2001)

Production of a recombinant human basic fibroblast growth factor with a collagen binding domain - J. A. Andrades; J. A. Santamara; L. T. Wu; F. L. Hall; M. E. Nimni; J. Becerra (Protoplasma, 2001)

A high-resolution record of mire development and climatic change spanning the Late-glacial-Holocene boundary at Church Moss, Davenham (Cheshire, England) - P. D. M. Hughes; H. K. Kenward; A. R. Hall; F. D. Large (Journal of Quaternary Science, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Abrupt deglaciation events and Holocene palaeoceanography from high-resolution cores, Cartwright Saddle, Labrador Shelf, Canada - J. T. Andrews; L. Keigwin; F. Hall; Anne E. Jennings (Journal of Quaternary Science, 1999)

Abrupt deglaciation events and Holocene palaeoceanography from high‐resolution cores, Cartwright Saddle, Labrador Shelf, Canada - J. T. Andrews; L. Keigwin; F. Hall; Anne E. Jennings (Journal of Quaternary Science, 1999)

Mus and Peromyscus chromosome homology established by FISH with three mouse paint probes - Wallace D. Dawson; S. Robert Young; Zongren Wang; Linda W. Liu; Ira F. Greenbaum; Lisa M. Davis; Bryan K. Hall (Mammalian Genome, 1999)

Effects of isolation-rearing on voluntary consumption of ethanol, sucrose and saccharin solutions in Fawn Hooded and Wistar rats - F. S. Hall; S. Huang; A. Pert; M. Linnoila; G. W. Fong (Psychopharmacology, 1998)

Effects of isolation-rearing on locomotion, anxiety and responses to ethanol in Fawn Hooded and Wistar rats - F. S. Hall; S. Huang; G. W. Fong; A. Pert; M. Linnoila (Psychopharmacology, 1998)

The Myxoma Virus EcoRI-O Fragment Encodes the DNA Binding Core Protein and the Major Envelope Protein of Extracellular Poxvirus - Ronald J. Jackson; Diana F. Hall (Virus Genes, 1998)

The use of an automated cell tracking system to identify specific cell types competent for regeneration and transformation - F. A. Krens; H. A. Verhoeven; A. J. Van Tunen; R. D. Hall (In Vitro Cellular & Developmental Biology - Plant, 1998)

The role of striatal dopaminergic mechanisms in rotational behavior induced by phencyclidine and phencyclidine-like drugs - A. Mele; Krystyna M. Wozniak; F. S. Hall; A. Pert (Psychopharmacology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Candidate Recombinant Vaccine Antigens ofTheileria Annulata: Current Status and Future Prospects - A. Tait; N. Boulter; C. d’Oliveira; F. Jongejan; C. G. D. Brown; S. Williamson; B. R. Shiels; F. McDonald; F. R. Hall (Tropical Animal Health and Production, 1997)

Phylogenetic Affinities Among the Extant Malagasy Lemurs (Lemuriformes) Based on Morphology and Behavior - Kathrin F. Stanger-Hall (Journal of Mammalian Evolution, 1997)

Fibromyalgia antirheumatic drug trials: Effects of a standardized instructional videotape on the reliability of observer-dependent outcome measures - N. Bellamy; R. Buchbinder; S. Hall; P. Lowthian; M. R. Patrick; P. F. J. Ryan; A. Stockman; G. Grant; S. Green; J. Campbell (Inflammopharmacology, 1997)

New Zealand's Privatization of Forest Lands: Policy Lessons for the United States and Elsewhere? - O. F. Hall (Forest Science, 1997)
Two forest policy questions are examined: 1. What particular problems in New Zealand's privatization of public forest lands (1985 to 1995) need thorough examination prior to proposing it in the United States or elsewhere? 2. What light does the New Zealand experience throw on the question of whether privatization and subdivision of forest lands is the solution to multiple use conflicts among forest land uses and users? A brief history of the origin and implementation of New Zealand's forest privatization policy is given, including the disestablishment of its national Forest Service. Two unique features of New Zealand made privatization especially appropriate there: the history of many government-operated businesses, and the great area and productivity of a very distinctive and differentiated forest type—radiata pine plantations. Nine objectives of privatization stated in New Zealand, 5 specifically on forestry, are analyzed. Six of the 9 were concluded to be successful in New Zealand. Possibilities of success in the United States are examined. As a solution for multiple-use problems, both positive and negative results of the policy are found. Finally, 6 tentative "lessons" are concluded that should be reviewed in countries where a similar policy is proposed: 1. Privatization should involve either leasing or fee simple sale of forested land primarily suited to rapid tree growth of commercially valuable species suitable for being managed for successive crops of timber at a profit, with covenants for regeneration after harvest. 2. Lands critical for recreational, aesthetic, or habitat values should remain publicly owned. 3. Lands on which re-investment of some of the income in regeneration is of questionable profitability should not be entered into the policy. 4. The policy could be successful in avoiding many but not all multiple-use conflicts for the managers. 5. In public forests retained for exclusively noncommodity uses, questions of the availability of some useful and valuable woods may require arbitration of conflicts. 6. Privatization doesn't solve the struggle to financially support park and wilderness and special wildlife habitat. For. Sci. 43(2):181-193.

An outline tephrochronology for the Holocene of the north of Ireland - JONATHAN R. PILCHER; VALERIE A. HALL; F. GERRY McCORMAC (Journal of Quaternary Science, 1996)

An outline tephrochronology for the Holocene of the north of Ireland - JONATHAN R. PILCHER; VALERIE A. HALL; F. GERRY McCORMAC (Journal of Quaternary Science, 1996)

The application of biological pesticides: Limitations and a practical solution - A. C. Chapple; R. A. Downer; T. M. Wolf; R. A. J. Taylor; F. R. Hall (BioControl, 1996)

Characterization of the tobacco glycoprotein surface binding property of heart and skeletal muscle cells - Charles A. Santos-Buch; Harry R. Hall; Fausto Farfan; Irene Orlow; Adolfo Firpo; Betsy F. von Kreuter; Carl G. Becker (Archives of Toxicology, 1995)

Human herpesvirus-6 strain groups: a nomenclature - D. Ablashi; H. Agut; Z. Berneman; G. Campadelli-Fiume; D. Carrigan; L. Ceccerini-Nelli; B. Chandran; S. Chou; H. Collandre; R. Cone; T. Dambaugh; S. Dewhurst; et al. (Archives of Virology, 1993)

Physical mapping and field inversion gel electrophoresis ofAmsacta moorei entomopoxvirus DNA - R. L. Hall; W. F. Hink (Archives of Virology, 1990)

Laboratory studies on the biology ofSpalangia nigra [Hym.: Pteromalidae] - R. D. Hall; F. J. Fischer (BioControl, 1988)

Aristolochic acid is mutagenic and recombinogenic in Drosophila genotoxicity tests - H. Frei; F. E. Würgler; H. Juon; C. B. Hall; U. Graf (Archives of Toxicology, 1985)

Dislodgeable azinphosmethyl residues from air blast spraying of apple foliage in Ohio - F. R. Hall; D. L. Reichard; H. R. Krueger (Archives of Environmental Contamination and Toxicology, 1975)